Judgment and Decision-Making Activities of Government Executives as Described by Superiors and Co-Workers - Forehand, Garlie A.; Guetzkow, Harold (Management Science, 1962)
Concepts which may be useful in research on executive performance stem from a variety of sources and are expressed in a variety of vocabularies. Administrators themselves have developed a complex jargon which is likely to be as mystifying to the social scientists as is the latter's to them. Administrative theorists often formulate variables in the language of psychology [10] in order to pose problems and suggest hypotheses for study. The translation of ideas from practitioner's lore or administrative theory into behavioral terms amenable to measurement, however, raises a host of conceptual and methodological questions. Some of these questions are confronted in the present study. It is one of a series of papers intended to develop a general theory of “executive judgment” and to permit study of its susceptibility to educational modification. An a priori analysis of the concept of executive judgment which provides the rationale of these studies is presented elsewhere [Guetzkow, H., G. A. Forehand. 1961. A research strategy for partial knowledge useful in the selection of executives. R. Tagiuri, ed. Research Needs in Executive Selection. Harvard Business School, Boston.].